2021
DOI: 10.1515/jcim-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-alcoholic extract of Morus nigra reduces fasting blood glucose and HbA1c% in diabetic patients, probably via competitive and allosteric interaction with alpha-glucosidase enzyme; a clinical trial and in silico analysis

Abstract: Objectives 1-Deoxynojirimycin (1-DNJ), the main active component found in Morus nigra (black mulberry) is reported to be effective in controlling diabetes. We have evaluated the effect of hydro-alcoholic extract of M. nigra leaves on the fasting blood glucose (FBS) and hemoglobin A1c% (HbA1c%) in diabetic patients. Furthermore, we compared the interaction of 1-DNJ and glucose molecules with the alpha-glucosidase enzyme, which has a critical role in the lysis of glucose-based polymers in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The clinical trial and virtual analysis showed that a hydro-alcoholic extract of black mulberry ( M. nigra ) leaf may be efficient in decreasing FPG and HbA1c in diabetic patients. 60 The study conducted with 37 adult participants proved that the difference in the positive incremental area under the curve ((pIAUC) for glucose concentration over 120 minutes) for 125, 250, and 500 mg mulberry extract compared with placebo was −6.1% ( p = 0.316), −14.0% ( p = 0.022), and −22.0% ( p < 0.001), respectively. 61 1-DNJ is an effective inhibitor of α-glucosidase, which is an enzyme that breaks down starch and other disaccharides into glucose.…”
Section: Discussionmentioning
confidence: 97%
“…The clinical trial and virtual analysis showed that a hydro-alcoholic extract of black mulberry ( M. nigra ) leaf may be efficient in decreasing FPG and HbA1c in diabetic patients. 60 The study conducted with 37 adult participants proved that the difference in the positive incremental area under the curve ((pIAUC) for glucose concentration over 120 minutes) for 125, 250, and 500 mg mulberry extract compared with placebo was −6.1% ( p = 0.316), −14.0% ( p = 0.022), and −22.0% ( p < 0.001), respectively. 61 1-DNJ is an effective inhibitor of α-glucosidase, which is an enzyme that breaks down starch and other disaccharides into glucose.…”
Section: Discussionmentioning
confidence: 97%
“…DNJ is a potential antihyperglycaemic compound in mulberry leaves as it inhibits glucosidase, suppress abnormally high level of blood glucose and prevent diabetes mellitus (Ramappa et al, 2020;Tang et al, 2023). Furthermore, glucose and DNJ are similar in structures that is why DNJ blocks the main active sites of glucose degrading enzymes; so inhibits the carbohydrates digestion and absorption (Momeni et al, 2021;Mohamed et al, 2023). DNJ is known as a cofactor and help in controlling postprandial blood glucose; also helps in degrading the oligosaccharides and starch to monosaccharides before their absorption (Liu et al, 2015).…”
Section: Alkaloidsmentioning
confidence: 99%
“…In the study of Momeni et al (2021) 1 tablet/day white mulberry 50 mg, I. paraguariensis 1,000 mg, and chromium picolinate 100 μg 3 months FPG, PPG, HbA 1c , and HOMA index decrease M value increase Derosa et al (2021) Abbreviations: 1,5AG, 1,5-anhydroglucitol; FPG, fasting plasma glucose; FPI, fasting plasma insulin; GA, glycated albumin; HbA 1c , glycated hemoglobin; HOMA-IR, homeostatic model assessment of insulin resistance; iAUC, incremental area under the curve; IFG, impaired fasting glucose; IGT, impaired glucose tolerance; OGTT, oral glucose tolerance test; PPG, post-prandial plasma glucose; PPI, post-prandial plasma insulin; SMBG, self-monitoring blood glucose; T2DM, type 2 diabetes mellitus.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…In the study of Momeni et al ( 2021 ) 100 T2DM patients were treated with 3 ml of 4% hydroalcoholic extract of M. nigra leaves or placebo in water, thrice a day, for 3 months. It has been observed that the supplement significantly decreased FPG (−21.00 mg/dl, −11.52%, p < .001) and HbA 1c (−1.10%, −15.21%, p < .001) compared to baseline values (Momeni et al, 2021 ).…”
Section: Nutraceuticalsmentioning
confidence: 99%